PENGARUH PELAKSANAAN PENETAPAN HARGA PRODUK TERHADAP MINAT KONSUMEN (KASUS PENJUALAN MOBIL TOYOTA AVANZA PADA PT. AGUNG AUTOMALL CABANG PEKANBARU) - Resi Fibrianti; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is a problem in any decline in consumer interest for buy a car Toyota Avanza, indicated by decline in sales by 2012 compared with 2011. As for the purpose of this research is to know the implementation of pricing and consumer interest against Toyota Avanza car on PT Agung Automall branch of Soweto as well as to know how the implementation of pricing products of consumer interest buying a car on PT. Supreme Avanza Automall branch of Soweto. Results of the study concluded that implementation of the Avanza car pricing on PT Agung Automall located on Soweto area Branch agree, which means consumers agree with car pricing Toyota Avanza on this present moment. Consumer interest in car Avanza in PT Agung Automall branch of Soweto is the interest, meaning consumers will love the car Toyota Avanza, and selected him to be the primary choice and certain options that ultimately consumers make a purchase the Toyota Avanza car and also recommend it to others. The results of data analysis through SPSS program, note that the independent variable (pricing) have a strong link to the dependent variable (the interest of consumers). Car pricing Toyota Avanza implemented by PT Agung Automall branch of Soweto give a positive and significant effect against the interests of consumers, so if the pricing policy is implemented properly, it will give rise to an increase in the interest of consumers.Key words: Pricing, Consumer Interest, The Toyota Avanza